Study of clinical profile and pattern of stroke in diabetic and non-diabetic patients in a hospital of Kumaon region - Deepali Joshi; Mohd Maroof; Subhash Chandra Joshi; Vivekanand Satyawali (Asian Journal of Medical Sciences, 2022)
Background: Diabetes enhances the risk of stroke which is one of the leading causes of morbidity and mortality. Aims and Objectives: The study was done to analyze the clinical profile and pattern of stroke in diabetic and non-diabetic patients. Materials and Methods: This was a hospital-based cross-sectional study done in 130 stroke patients (with/without diabetes – 65 each) presenting to outpatient departmentdepartment general medicine department, Dr. Sushila Tiwari Hospital of Government Medical College, Haldwani during January 2020–September 2021. A detailed history, neurological examination along with assessment of risk factors, pattern, and subtype were done. Results: The mean age was significantly higher among stroke patients with diabetes (66.38±11.99 years). The proportion of systemic hypertension was significantly higher in stroke patients without diabetes (89.2%). Abnormal ECG was significantly more reported in stroke patients without diabetes (73.8%). The mean hemoglobin and mean random blood sugar were significantly higher in stroke patients with diabetes (8.82±1.72 and 291.17±107.39, respectively). The mean high-density lipoprotein was significantly higher in stroke patients without diabetes (43.06±5.1), whereas mean low-density lipoprotein, mean triglycerides, and mean total cholesterol were significantly higher in stroke patients with diabetes (126.28±33.19; 186.97±45.91; and 229.31±39.83, respectively). The presenting complaints observed were altered consciousness (67.7%) right hemiparesis (55.4%), left hemiparesis (41.5%), abnormal body movement (28.5%), etc. Ischemic stroke was significantly higher in patients with diabetes (90.8%). Lacunar (34%), basal ganglia (27%), cortical (23%), etc., were stroke subtypes seen among study patients. Conclusion: Significant difference was observed between stroke patients with/without diabetes in terms of age, several risk factors, presenting symptoms, pattern, and its subtype.